Analisis Limbah Kelapa Sawit Sebagai Bahan Bakar Boiler dengan Menggunakan Variasi Campuran Antara Fiber dan Cangkang Buah Sawit - Jatmiko Edi Siswanto (Journal of Electrical Power Control and Automation (JEPCA), 2020)
The growth of the palm oil management industry in Jambi which has an impact on the increasing size of palm oil management holidays include Fiber and Shells. Each processing of 1 ton of FFB produces 120 kg of fiber and produces 50 kg of shells. Where the two wastes have a high calorific value and thousands of tons of FFB are processed in Jambi every month. In this analysis will analyze the composition of combustion using fiber and shell to get the highest calorific value on the Boiler, where the composition analyzed is the ratio of 100% Fiber, 75% Fiber 25% Shell, 50% Fiber 50% Shell, 25% Fiber 75% Shell 100% shell. The results of research analysis The heating value of fiber and shell composition variations ranged from 14978,053 kJ/kg to 15463,083 kJ/kg. With the highest heating value is 100% fiber composition (15463,083 kJ / kg), and the lowest heating value is 100% shell composition. (14978,053 kJ/kg). The composition that gives the highest profit is the composition of 100% fiber. With the details of the value of water content, air requirements, low flue gas, and also produces a high heating value.